Citizenship Identity in the Context of Dayak Ethnic Transnationalism: Between State, Costum, and Cross-Border Mobility - Dewantara, Jagad Aditya; Budimansyah, Dasim; Prasetiyo, Wibowo Heru; Rachman, Fazli; Sulistyarini; Gida Kadarisma (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
This paper examines the civic identity of the Dayak people in the West Kalimantan border region within the context of ethnic transnationalism, emphasizing the role of custom and cross-border mobility. Recognizing that Dayak communities have historically lived beyond the boundaries of modern states, the study conceptualizes citizenship as a lived social experience that does not always align with nation-state logic. Using ethnographic methods, the research explores how Dayak people interpret citizenship through everyday practices, kinship relations, and cross-border interactions. The findings show that citizenship is understood situationally and pragmatically, particularly in relation to administrative needs and access to state services, while ethnic and customary identities remain the primary basis of social loyalty. Custom functions as a value framework regulating community membership, social relations, and attachment to ancestral lands across borders. Continuous mobility sustains a transnational social space where borders are negotiated administrative structures rather than rigid social boundaries. The study highlights the layered and dynamic nature of border citizenship and contributes to scholarship on indigenous transnationalism.